2020
DOI: 10.1371/journal.pone.0235686
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation recovery during walking is impacted by knowledge of perturbation timing in below-knee prosthesis users and non-impaired participants

Abstract: Previous research found that below-knee prosthesis users proactively increase their lateral margin-of-stability on their impaired side in anticipation of an impending perturbation when the timing is predictable and potentially directed toward the impaired limb. While knowledge of perturbation timing and direction influences proactive strategies, the consequences of such knowledge and anticipatory behavior on recovery from perturbations is unclear. This study characterized center-of-mass (CoM) dynamics of below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 44 publications
3
19
1
1
Order By: Relevance
“…However the findings of the present study seems to only partially conform to the results of other studies that have investigated dynamic balancing responses following unexpected perturbing pushes in the frontal plane applied to the pelvis of UTA subjects [ 23 , 24 ]. Namely UTA subjects in those studies developed stepping responses regardless whether the non-amputated or amputated leg was in stance phase at the time of perturbation [ 23 , 24 ] whereas in the present study UTA subjects applied in-stance and not stepping strategy when they counteracted outward-directed perturbation on the non-amputated side. Discrepancy between studies is to be attributed to different walking speeds which was in those studies 0.8 m/s whereas in in the present study it was set to 0.5 m/s to match the average walking speed of UTA subjects after discharge [ 1 ].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…However the findings of the present study seems to only partially conform to the results of other studies that have investigated dynamic balancing responses following unexpected perturbing pushes in the frontal plane applied to the pelvis of UTA subjects [ 23 , 24 ]. Namely UTA subjects in those studies developed stepping responses regardless whether the non-amputated or amputated leg was in stance phase at the time of perturbation [ 23 , 24 ] whereas in the present study UTA subjects applied in-stance and not stepping strategy when they counteracted outward-directed perturbation on the non-amputated side. Discrepancy between studies is to be attributed to different walking speeds which was in those studies 0.8 m/s whereas in in the present study it was set to 0.5 m/s to match the average walking speed of UTA subjects after discharge [ 1 ].…”
Section: Discussionsupporting
confidence: 81%
“…Unlike proactive gait adaptations reactive responses of UTA subjects have been addressed in the literature less extensively. Experiments where perturbing pushes were delivered to the pelvis in the frontal plane [ 23 , 24 ] showed that UTA subjects use proactive adaptations only if the timing of perturbation is predictable and when perturbation is delivered on their amputated side [ 23 ]. They also showed that if perturbation timing is known peak COM displacement is smaller [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations